Process systems engineering perspectives on eco-efficient downstream processing of volatile biochemicals from fermentation - Janković, Tamara; Straathof, Adrie J. J.; Kiss, Anton A. (Frontiers in Energy Research, 2024)
Increasing concerns over environmental pollution, climate change and energy security are driving a necessary transition from fossil carbon sources to more sustainable alternatives. Due to lower environmental impact, biochemicals are rapidly gaining significance as a potential renewable solution, particularly of interest in Europe. In this context, process systems engineering (PSE) helps with the decision-making at multiple scales and levels, aiming for optimum use of (renewable) resources. Fermentation using waste biomass or industrial off-gases is a promising way for the production of these products. However, due to the inhibitory effects or low substrate concentrations, relatively low product concentrations can be obtained. Consequently, significant improvements in downstream processing are needed to increase the competitiveness of the overall bioprocesses. This paper supports sustainable development by providing new PSE perspectives on the purification of volatile bioproducts from dilute fermentation broths. Since purification significantly contributes to the total cost of biochemical production processes (20%–40% of the total cost), enhancing this part may substantially improve the competitiveness of the overall bioprocesses. The highly advanced downstream process offers the possibility of recovering high-purity products while enhancing the fermentation step by continuously removing inhibitory products, and recycling microorganisms with most of the present water. Besides higher productivity, the upstream process can be greatly improved by avoiding loss of biomass, enabling closed-loop operation and decreasing the need for fresh water. Applying heat pumping, heat integration and other methods of process intensification (PI) can drastically reduce energy requirements and CO2 emissions. Additionally, the opportunity to use renewable electricity instead of conventional fossil energy presents a significant step toward (green) electrification and decarbonization of the chemical industry.